Implementation and application of "One Network Unlimited" medical internet of things / Dou Huan and Mohd Rafiz Salji - Huan, Dou; Salji, Mohd Rafiz (2023)
This paper introduces the implementation and application of "One Network Unlimited" medical Internet of Things (IoT). It introduces the implementation methods of "One Network Unlimited" medical IoT, including sensor technology, intelligent embedding, RFID and cloud computing technology. The specific applications of the "One Network Unlimited" medical IoT are discussed by using the literature analysis method. Through the introduction of this paper, we can see that "one network infinite" medical IOT has a wide application prospect in hospital management, which can improve hospital management efficiency and service quality, and provide patients with safer, more comfortable, and more convenient medical services.